The Impact of the Global Financial Crisis on Australian Banking Efficiency (International Journal of Banking and Finance, 2016)
The theory of financial stability postulates that financial institutions in a country experiencing financial crisis would witness productivity losses. This study examined whether they experience productivity losses when there is no crisis, and whether the financial sector is not immune from global economic events. The Australian financial institution efficiency and productivity during 1999-2009 were examined, that is, after the financial system reforms but the test period includes the financial crisis years. Efficiency scores were computed using Stochastic Frontier Analysis and total factor productivity using Malmquist indices. Australian institutions were found to have experienced productivity decline during the global financial crisis. The evidence is just the opposite of the common belief that Australian institutions remained insulated from the crisis. Global economic slowdown can also lead to productivity losses in a country not experiencing severe financial crisis because of the reforms taken long before the crisis to improve prudential oversight of the financial institutions in Australia.